2024
DOI: 10.1371/journal.pgph.0002451
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized trial of client and provider-directed financial interventions to align incentives with appropriate case management in retail medicine outlets: Results of the TESTsmART Trial in western Kenya

Jeremiah Laktabai,
Emmah Kimachas,
Joseph Kipkoech
et al.

Abstract: ACTs are responsible for a substantial proportion of the global reduction in malaria mortality over the last ten years, made possible by publicly-funded subsidies making these drugs accessible and affordable in the private sector. However, inexpensive ACTs available in retail outlets have contributed substantially to overconsumption. We test an innovative, scalable strategy to target ACT-subsidies to clients with a confirmatory diagnosis. We supported malaria testing(mRDTs) in 39 medicine outlets in western Ke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Study results in western Kenya, in which we implemented a similar trial, also found little impact of the intervention on testing uptake or targeting of ACTs. Across both sites, we found testing uptake highly heterogeneous among PMRs with many clients testing negative purchasing antimalarials and most clients foregoing testing altogether while purchasing ACTs or other antimalarials [ 11 ]. Clients testing positive in both countries also spent more (and purchased more drugs) compared to untested patients or patients testing negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study results in western Kenya, in which we implemented a similar trial, also found little impact of the intervention on testing uptake or targeting of ACTs. Across both sites, we found testing uptake highly heterogeneous among PMRs with many clients testing negative purchasing antimalarials and most clients foregoing testing altogether while purchasing ACTs or other antimalarials [ 11 ]. Clients testing positive in both countries also spent more (and purchased more drugs) compared to untested patients or patients testing negative.…”
Section: Discussionmentioning
confidence: 99%
“…This study is linked to a similar cluster randomized controlled trial in the contrasting rural study site of the region around Webuye in western Kenya. These results are published elsewhere [ 11 ]. Full details of the study design were previously reported in Woolsey et al [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 97%